Tune it out - Sumner, Jamie (Atheneum Books for Young Readers, 2020)
"Twelve-year-old Lou Montgomery's life has been centered on her mother's terrifying plan to make her a singing star, but a crisis reveals Lou's sensory processing disorder and people determined to help her address it"--Provided by publisher.